Convective Hydration of the Upper Troposphere and Lower Stratosphere. Issue 9 (6th May 2018) - Schoeberl, Mark R.; Jensen, Eric J.; Pfister, Leonhard; Ueyama, Rei; Avery, Melody; Dessler, Andrew E.
Abstract: We use our forward domain filling trajectory model to explore the impact of tropical convection on stratospheric water vapor (H2 O) and tropical tropopause layer cloud fraction (TTLCF). Our model results are compared to winter 2008/2009 TTLCF derived from Cloud‐Aerosol Lidar with Orthogonal Polarization and lower stratospheric H2 O observations from the Microwave Limb Sounder. Convection alters the in situ water vapor by driving the air toward ice saturation relative humidity. If the air is subsaturated, then convection hydrates the air through the evaporation of ice, but if the air is supersaturated, then convective ice crystals grow and precipitate, dehydrating the air. On average, there are a large number of both hydrating and dehydrating convective events in the upper troposphere, but hydrating events exceed dehydrating events. Explicitly adding convection produces a less than 2% increase in global stratospheric water vapor during the period analyzed here. Tropical tropopause temperature is the primary control of stratospheric water vapor, and unless convection extends above the tropopause, it has little direct impact. Less than 1% of the model parcels encounter convection above the analyzed cold‐point tropopause. Convection, on the other hand, has a large impact on TTLCF. The model TTLCF doubles when convection is included, and this sensitivity has implications for the future climate‐related changes, given that tropical convective frequency and convective altitudes may change. Plain Language Summary: Deep convection has been invoked as a significant source for stratospheric water vapor based on aircraft observations. This modelling study shows that deep convection plays almost no role in directly hydrating the stratosphere because deep convection rarely penetrates the tropopause 'cold trap' that largely controls stratospheric water vapor. Key Points: Tropical convection increases stratospheric water vapor, but by less than 2% Only convection that penetrates the tropical tropopause significantly impacts stratospheric water Tropical convection is a major source of upper tropospheric clouds